1992
DOI: 10.1021/bi00147a002
|View full text |Cite
|
Sign up to set email alerts
|

Functional topology of a surface loop shielding the catalytic center in lipoprotein lipase

Abstract: Lipoprotein lipase (LPL), hepatic lipase, and pancreatic lipase show high sequence homology to one another. The crystal structure of pancreatic lipase suggests that it contains a trypsin-like Asp-His-Ser catalytic triad at the active center, which is shielded by a disulfide bridge-bounded surface loop that must be repositioned before the substrate can gain access to the catalytic residues. By sequence alignment, the homologous catalytic triad in LPL corresponds to Asp156-His241-Ser132, absolutely conserved res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 23 publications
1
15
0
2
Order By: Relevance
“…Ser 267 , although not the acyl-accepting serine residue within the catalytic site, is nonetheless highly conserved, being found in all members of the lipase gene family in all species. 31 Faustinella et al 32 demonstrated that mutagenesis of this serine to alanine in lipoprotein lipase resulted in a protein that was expressed but had greatly reduced activity. Indeed, Ser 267 is adjacent to the a-helical "flap" region (or lid domain) present in all lipases, which is presumably responsible for lipase interfacial activation 33 and is only 10 residues away from the histidine residue contributing to the serine-histidine-aspartate catalytic triad.…”
Section: Discussionmentioning
confidence: 99%
“…Ser 267 , although not the acyl-accepting serine residue within the catalytic site, is nonetheless highly conserved, being found in all members of the lipase gene family in all species. 31 Faustinella et al 32 demonstrated that mutagenesis of this serine to alanine in lipoprotein lipase resulted in a protein that was expressed but had greatly reduced activity. Indeed, Ser 267 is adjacent to the a-helical "flap" region (or lid domain) present in all lipases, which is presumably responsible for lipase interfacial activation 33 and is only 10 residues away from the histidine residue contributing to the serine-histidine-aspartate catalytic triad.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [17][18][19][20][21][22]. However, the structural basis of LPL in its noncatalytic role to act as a bridge for circulating lipoproteins and their receptors is poorly understood.…”
mentioning
confidence: 99%
“…By taking advantage of these fibroblast-like cells that can be readily induced to produce wild-type and mutant LPLs by transfection (17)(18)(19)24), we have analyzed the structural requirement for the effect of LPL in LDL receptor-mediated uptake and catabolism of normal human VLDL. Our results indicate that in these cells, the LDL receptor can bind to and catabolize VLDL in the presence of LPL.…”
mentioning
confidence: 99%
“…Although these two loops differ in primary sequence, they both show a similar predicted (by the Chou-Fasman algorithm) alternation of a-helical and P-sheet regions. However, replacement of the human LPL loop with the loop from pancreatic lipase yields an inactive human LPL [17].…”
mentioning
confidence: 99%